Efeito dos níveis de energia da ração sobre o desempenho e teor de gordura na carcaça de frangos de corte - Bernal, F. E. Moreno [UNES`P]; Baião, N. C. (Arquivo Brasileiro Medicina Veterinaria Zootecnia, 1996)
It was studied the effect of energy levels in the diet, obtained from vegetal oil inclusion, on the performance, diet cost per kilogram of broiler and fat content of the carcass, There were used 4,800 broiler chicks, 2,400 males and 2,400 females, and they were distributed in six treatment (energy levels in kcal ME/kg of diet) in three different phases: start diet from one to 20 days of age: A - 2930, B - 2980, C - 3030, D - 3080, E - 3130, F - 3180, growth diet from 21 to 40 days: A - 2980, B - 3030, C - 3050, D - 3130, E - 3150, F - 3230, finishing diet from 41 to 45 days of age: A - 3030, B - 3080, C - 3130,, D - 3180, E - 3230, F - 3280. The protein content was 22, 20 and 18% in each phase, respectively, There were evaluated the feed intake, energy intake, protein intake, weight gain, feed conversion mortality, diet cost per kg/bw. Sixty broilers were slaughtered, five males and five females per treatment, randomly chosen to determine the carcass composition considering the dry matter content, lipids content and protein content, total fat in carcass and fat per kilogram of broiler. The data were submitted to variance analysis and the means were compared using SNK. The broilers fed with medium and low levels of dietary energy showed the highest weight gain. At energy levels of the treatment D in the three phases, the lowest cost per kilogram of broiler was obtained. The females presented the highest fat content per kilogram of broiler produced.
Effect of energy ration levels on the performance and carcass fat content of chicken
Keywords: energy; fat; carcass; chicken